Helminths parasites of digestive trackt of sheep and goats in Macedonian region - THEODORIDIS (Ι. ΘΕΟΔΩΡΙΔΗΣ), Y.; HIMONAS (Χ. ΧΕΙΜΩΝΑΣ), C.; PAPAZAHARIADOU (Μ. ΠΑΠΑΖΑΧΑΡΙΑΔΟΥ), M. (Journal of the Hellenic Veterinary Medical Society, 2018)
During two periods (December 1985-October 1986 and October 1990-April 1991), the digestive tracts of 102 sheep and 29 goats were examined, with the purpose to find out and identify the helminthes parasites of these animals. The 96,1% of sheep and 93,1% of goats were found to be infected with 26 and 20 different helminths, respectively. The nematodes which were found out of the different parts of the digestive tract of these animals were: Sheep: oesophagus: Gongylonema pulchrum, abomasum: Haemonchus contortus, Teladorsagia circumcincta, T. trifurcata, Trichostrongylus axei and Cooperia oncophora, small intestine: Teladorsagia circumcincta, Trichostrongylus colubriformis} T. vitrinus, T. capricola, Cooperia oncophora, C. curticei, Nematodirus filicollis, N. helvetianus, N. spathiger, N. battus, Bunostomum trigonocephalum and Strongyloides papillosus, large intestine: Oesophagostomum venulosum, Oe. columbianum, Chabertia ovina, Trichuris globulosa, T. ovis and Skrjabinema ovis. Goats: all the previous findings except T. vitrinus, Nematodirus helvetianus, N. battus and Trichuris ovis. The cestodes parasites, Moniezia expansa, Moniezia benedni, Avitellina centripunctata and Stilesia globipunctata were found into the small intestine of sheep and, Moniezia expansa and Avitellina centripunctata, in goats only. All animals were infected with more than one different parasites. The sheep nematodes Cooperia curticei, Nematodirus helvetianus, and N. spathiger, were identified for the first time in Greece, more over, Nematodirus battus were found out and identified for the first time in Greece.